From Cold to Code War: Dissecting Security Strategies for the Cyberspace Strategic Environment and Identifying Cyber Risks to the Nuclear Strategic Environment - Salik, Hammaad; Zahid, Rao Ibrahim (Cyberpolitik Journal, 2022)
Due to its effectiveness in the Cold War, the security strategy of Nuclear Deterrence has left a seemingly irrefutable imprint on the minds of strategists and policymakers. Nuclear Deterrence is an iteration of conventional deterrence, whereas both enjoy a generalized applicability status in the context of all strategic environments. The ultimate objective of applying these security strategies to any strategic environment is achieving stability. However, as innovative technologies emerge and disparate strategic environments unfold, it becomes critical to evaluate the applicability of nuclear or conventional deterrence as an effective security strategy for these environments. It also becomes critical to analyze the effects of these novel strategic environments on the stability of an international system historically established in all preceding environments. This article explains the variance of approach and mentality when conceptualizing strategic nuclear and strategic cyberspace environments. It then explores the fundamental core differences of these strategic environments which validate such a variance. The article then focuses on how deterrence may not be a viable security strategy for the cyberspace environment before discussing some of the impacts the cyberspace environment may have on the nuclear environment. These impacts have been discussed as risks to the nuclear environment and may have a destabilizing effect on the stability that has been established via nuclear deterrence in the strategic nuclear environment.